Communication Behaviour of Fish Farmers of the FFPO on Scientific Fish Farming - Mondal, Abdul Hannan; Dana, Shyam Sundar; Ray (Sarkar), Moumita; Kumari, Nandita; Karjee, Ritika (Indian Journal of Extension Education, 2024)
The study examined the communication behaviour of within Fish Farmers Producer Organizations (FFPO) in the Purba Medinipur District of West Bengal in 2023. Using a descriptive research design, data were collected from 120 fish farmers representing four FFPOs in the district. 62.5 per cent regularly contacted fellow farmers for information among (personal localite channels) and, 57.5 per cent reached out to private company consultants, extension workers, or input dealers (personal cosmopolite channels). In terms of impersonal cosmopolite channels, 95 per cent used mobile apps and the Internet as their primary sources of fish-farm-related information. Fish farmers predominantly used personal localite channels to purchase improved seed varieties (80.83%) and feeding practices (72.5%). Personal cosmopolite channels were mainly employed to avail financial benefits (79.16%) and disease diagnosis and management (76.66%). Impersonal cosmopolite channels were utilized less, with 24.16 per cent for marketing and branding. Regarding information-processing behaviour, most respondents evaluated information through discussions with fellow farmers (67.5%) and deliberation based on previous experiences (34.16%). Information storage was accomplished through memorization (75.83%). Most respondents transferred information by sharing with their fellow members for localized awareness (27.5%). Implementing strategies like regular training, promoting information exchange, and utilizing extension services can improve the communication behaviour of fish farmers within FFPO.
Keywords: Communication; Fish Farmers Producer Organizations (FFPO); Fish farmers; Information-processing behaviour